Identification of Ectoparasites and Gastrointestinal Parasites in Eurasian Tree Sparrow (Passer montanus) - Moh. Ilham Rizkul Ulum; Mochamad Lazuardi; Nunuk Dyah Retno Lastuti; Poedji Hastutiek; Soeharsono Soeharsono; Amirul Muslim Amrullah (Universitas Airlangga, 2022)
This study aims to determine the prevalence and identify ectoparasite and gastrointestinal parasites in Eurasian tree sparrow (Passer montanus) in Kediri Regency, East Java, Indonesia. The research was conducted in January 2021 with 100 samples of body swabs and feces of Eurasian tree sparrow. The examination was done in the Anugerah Satwa Veterinary Clinic in Kediri Regency using direct smear and flotation methods. The observations in this study showed that from 100 samples of body swabs, 38 samples (38%) were infested with ectoparasites which are Dermoglyphus sp. and Strelkoviacarus sp. and from 100 feces samples, 47 samples (47%) were infected with helminthic eggs with the single infections by Ascaridia sp. as much as 12%, Dispharynx sp. as much as 1% and mixed infections of Ascaridia sp. and Dispharynx sp. were 25%. Assessed by examination for the protozoa also found that Isospora sp. was present with prevalence of 100% of the 100 sparrow feces samples examined.